Effectiveness Between Daily and After-Each-Case Room Disinfection of the Endoscopy Unit - Jin, Bo; Hu, Yue; Huang, Liang; Cheng, Xiaoyun; Zhao, Jin; Yang, Xuejing; Sun, Xiling; Gan, Tieer; Lu, Bin (Frontiers in Public Health, 2021)
Background: To evaluate the effectiveness between daily and after-each-case room disinfection in the endoscopy unit. Methods: This study was conducted in an endoscopy unit of the First Affiliation of Zhejiang Chinese Medical University. We cultured samples from the surface of endoscopy unit items, including operation unit air, endoscopist's isolation gown, control panel buttons, workstation mouse, and patient's bed-head. All samples were divided into daily and after-each-case room disinfection groups. In addition, each group was subdivided into sedation and non-sedation gastroscopy and with and without ventilation room groups. Results: The qualified rate of patient bed-head samples was lower in the daily room disinfection group (76.67%) than in the after-each-case group (100%). The endoscopist’s isolation gown, mouse at the workstation, and patient bed-head demonstrated the lowest bacterial and fungal load in the disinfection group after-each-case of the room compared to the daily disinfection group (all p<0.05). In the subgroup analysis, a higher microbial load was observed for the endoscopist’s isolation gown used during non-sedation gastroscopy in an unventilated room under the after-each-case room disinfection pattern (p<0.05); a higher microbial load was observed for the control panel buttons during non-sedation gastroscopy under the after-each-case room disinfection pattern (p<0.05). Conclusions: For risk-free or low-risk patients, daily room disinfection provides the basic health requirements of the endoscopy procedure. However, it is better to adopt after-each-case room disinfection for the endoscopist's isolation gown and patient's bed-head. For high-risk patients, after-each-case room disinfection is more suitable for every endoscopy unit (www.ClinicalTrials.gov, NCT04399005).